The role of epithelial cell adhesion molecule N-glycosylation on apoptosis in breast cancer cells. Issue 3 (March 2017) - Zhang, Dandan; Liu, Xue; Gao, Jiujiao; Sun, Yan; Liu, Tingjiao; Yan, Qiu; Yang, Xuesong
Glycosylation of cell surface proteins plays an important role in the regulation of apoptosis. It has been demonstrated that knockdown of epithelial cell adhesion molecule promoted apoptosis, inhibited cell proliferation, and caused cell-cycle arrest. In this study, we investigated whether and how N-glycosylation of epithelial cell adhesion molecule influenced the apoptosis in breast cancer cells. We applied the N-glycosylation mutation epithelial cell adhesion molecule plasmid to express deglycosylation of epithelial cell adhesion molecule and then to study its function. Our results showed that deglycosylation of epithelial cell adhesion molecule promoted apoptosis and inhibited cell proliferation. Deglycosylation of epithelial cell adhesion molecule enhanced the cytotoxic effect of 5-fluorouracil, promoting apoptosis by downregulating the expression of the anti-apoptotic protein Bcl-2 and upregulating the expression of the pro-apoptotic proteins Bax and Caspase 3 via the extracellular-signal-regulated kinase 1/2 and c-Jun N-terminal kinase mitogen-activated protein kinase signaling pathways in MCF-7 and MDA-MB-231 cells. These findings are important for a better understanding of epithelial cell adhesion molecule apoptosis regulation and suggest epithelial cell adhesion molecule as a potential target for the treatment of breast cancer.